2004
DOI: 10.1128/mcb.24.22.9823-9834.2004
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Role of Mitochondrial Transcription Factor A in Maintenance of Human Mitochondrial DNA

Abstract: Mitochondrial transcription factor A (TFAM), a transcription factor for mitochondrial DNA (mtDNA) that also possesses the property of nonspecific DNA binding, is essential for maintenance of mtDNA. To clarify the role of TFAM, we repressed the expression of endogenous TFAM in HeLa cells by RNA interference. The amount of TFAM decreased maximally to about 15% of the normal level at day 3 after RNA interference and then recovered gradually. The amount of mtDNA changed closely in parallel with the daily change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
234
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(242 citation statements)
references
References 43 publications
5
234
0
3
Order By: Relevance
“…This finding led to the conclusion that mitochondrial transcription is a two-component system also in higher cells, much similar to the situation in yeast. However, this model is not easy to reconcile with findings from other laboratories that have demonstrated that TFAM is an essential mammalian transcription factor both in vivo and in vitro (6,15,22). We here investigate the role of TFAM for transcription initiation in a defined in vitro system.…”
mentioning
confidence: 64%
“…This finding led to the conclusion that mitochondrial transcription is a two-component system also in higher cells, much similar to the situation in yeast. However, this model is not easy to reconcile with findings from other laboratories that have demonstrated that TFAM is an essential mammalian transcription factor both in vivo and in vitro (6,15,22). We here investigate the role of TFAM for transcription initiation in a defined in vitro system.…”
mentioning
confidence: 64%
“…This protein has an additional role as an architectural protein, which is essential for the maintenance of mtDNA; therefore, it also serves as a limiting determinant for the mtDNA copy number 18, 19. Thus, the suppression of TFAM expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For double fluorescent staining, the floating sections were stained with the following combinations of the first antibodies for 48 h at 4°C: anti- (Kanki et al, 2004b). After washing with PBS, the sections were incubated with a mixture of 0.5% Alexa 488 anti-mouse IgG and Cy3 anti-rabbit IgG, 0.5% Alexa 488 anti-rabbit IgG and Cy3 anti-mouse IgG (GE Healthcare) for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, there is increasing evidence that TFAM plays an important role in maintaining mtDNA and regulating its copy number. The amount of mtDNA is closely correlated with the amount of TFAM but not with the transcription level, and the majority of TFAM molecules are involved in architecturally maintaining the higher structure of mtDNA (Kanki et al, 2004b). More recently, transgenic mice that overexpressed human TFAM under control of the ␤-actin promoter were generated and showed an increased copy number of mtDNA in the myocardium and the protection of the heart from mitochondrial dysfunction (Ikeuchi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%